Analysis of Normalized Difference Vegetation Index (NDVI) and High Biodiversity Potential in Rupat Subdistrict, Bengkalis Regency, Riau - Hanifah Ikhsani; Muhammad Ikhwan; Emy Sadjati (Journal of Global Sustainable Agriculture, 2026)
ABSTRACT Due to increasing human activity and climate change, Rupat District is facing environmental degradation and threats to biodiversity. Therefore, the objective of this study is to analyze the Normalized Difference Vegetation Index (NDVI) values and the potential for high biodiversity. The study was conducted from May 2024 to May 2025 in Rupat District, Bengkalis Regency, in the province of Riau. Sentinel satellite imagery from 2023-2024 was used for the NDVI analysis. Data were collected using the rapid survey method. Plant species were identified using vegetation analysis with the grid line method, and wildlife species were observed using direct and indirect techniques or interviews with local communities. Direct observations were carried out using a combination of the point abundance (PA) method and the strip transect method. The analysis of biodiversity potential used the weighted linear combination (WLC) method. The study revealed that Rupat Subdistrict in Bengkalis Regency has NDVI classes:non-vegetated land -1 < NDVI < -0.03; 1,610.91 ha (1.64%), very low vegetation -0.03 < NDVI < 0.15; 538.44 ha (0.55%), low vegetation 0.15 < NDVI < 0.25; 2,063.24 ha (2.10%), moderate vegetation 0.25 < NDVI < 0.35; 5,030.82 ha (5.12%); and high vegetation 0.35 < NDVI < 1; 88,989.44 ha (90.59%). The biodiversity classes in Rupat District consist of low (86,136.15 ha), medium (6,949.43 ha), and high (5,147.27 ha) classes.This is due to several factors, such as habitat homogeneity (e.g., monoculture, such as oil palm and industrial forest plantations), high degradation levels and a lack of microhabitats.